High-performance dopant-free conjugated small molecule-based hole-transport materials for perovskite solar cells. (February 2018) - Azmi, Randi; Nam, So Youn; Sinaga, Septy; Akbar, Zico Alaia; Lee, Chang-Lyoul; Yoon, Sung Cheol; Jung, In Hwan; Jang, Sung-Yeon
Abstract: Hole-transport materials are a crucial element influencing the efficiency, hysteresis, and stability of perovskite solar cells (PSCs). Current state-of-the-art hole-transport materials require additional oxidizing dopants to achieve sufficient hole-transport properties; however, these dopants are environmentally harmful while also deteriorating the stability of PSCs. The development of high-performance dopant-free hole-transport materials is an important goal in the field of PSCs. In this work, we developed novel conjugated small-molecule based dopant-free hole-transport materials for PSCs containing di(1-benzothieno)[3, 2-b:2′, 3′-d]pyrrole (DBTP) as a core unit. These small molecule hole-transport materials achieved higher hole mobility and interfacial charge transfer rates than optimally doped spiro-OMeTAD, the current-state-of-the-art hole-transport material. A low-temperature PSC device using a dopant-free small molecule hole-transport material displayed a PCE of 18.09% with negligible hysteresis, higher than a device using doped spiro-OMeTAD (17.82%). Notably, the hydrophobic nature of our dopant-free small molecule hole-transport materials afforded excellent air-storage stability of low-temperature PSCs (81% retention after 33 days), whereas the doped spiro-OMeTAD based PSCs rapidly degraded under identical conditions (< 1% retention after 33 days). Graphical abstract: High-performance dopant-free small molecule hole-transport-materials (SM-HTMs) for perovskite solar cells (PSCs) are developed. The SM-HTMs possess appropriate energy levels with sufficient hole mobility to function as efficient HTM for PSCs without additional dopants. A low-temperature PSC (L-PSC) device using a dopant-free SM-HTM displayed a PCE of 18.09% with high air-storage stability, which is superior to a device using doped spiro-OMeTAD. Highlights: Novel dopant-free hole-transport-materials for perovskite solar cells were developed. The face-on orientation enabled sufficiently high hole mobility without dopants. Low-temperature PSCs based on the dopant-free HTMs showed the efficiency of 18.09%. The dopant-free HTMs acted as passivation layers, providing excellent air stability.